2021
DOI: 10.1038/s41598-021-90301-8
|View full text |Cite
|
Sign up to set email alerts
|

Design of non-autonomous pH oscillators and the existence of chemical beat phenomenon in a neutralization reaction

Abstract: The beat in physical systems is a transparent and well-understood phenomenon. It may occur in forced oscillatory systems and as a result of the interference of two waves of slightly different frequencies. However, in chemical systems, the realization of the latter type of the beat phenomenon has been lacking. Here we show that a periodic titration of acid and alkaline solutions with each other using programmable syringe pumps in a continuous stirred-tank reactor exhibits the beat phenomenon in the temporal pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…When the time period of the forcing was too low compared to the natural time period of the system and the residence time of the chemical species, the forcing did not affect the characteristics of the system. In addition to this, similar behavior was found in a neutralization reaction when an acid solution was titrated periodically in antiphase with an alkaline solution in a CSTR by using various periodic inflow rate functions of the reagents . Our simulations, made in spatially extended systems, confirmed that periodic boundary conditions created by low-frequency forcing on the CSTR part might result in the modulation of spatiotemporal oscillations and forced spatiotemporal bursting in the gel part.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…When the time period of the forcing was too low compared to the natural time period of the system and the residence time of the chemical species, the forcing did not affect the characteristics of the system. In addition to this, similar behavior was found in a neutralization reaction when an acid solution was titrated periodically in antiphase with an alkaline solution in a CSTR by using various periodic inflow rate functions of the reagents . Our simulations, made in spatially extended systems, confirmed that periodic boundary conditions created by low-frequency forcing on the CSTR part might result in the modulation of spatiotemporal oscillations and forced spatiotemporal bursting in the gel part.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to this, similar behavior was found in a neutralization reaction when an acid solution was titrated periodically in antiphase with an alkaline solution in a CSTR by using various periodic inflow rate functions of the reagents. 34 Our simulations, made in spatially extended systems, confirmed that periodic boundary conditions created by low-frequency forcing on the CSTR part might result in the modulation of spatiotemporal oscillations and forced spatiotemporal bursting in the gel part. Synchronization can also be observed at high-frequency forcing in a TSFR.…”
Section: Discussionmentioning
confidence: 99%
“…To control for the effect of average RT differences related to age on learning and consolidation of knowledge, we transformed the data in the following way. We divided each participants’ raw RT values of each trial type and each epoch by their own average performance (i.e., average RT) in the first epoch of the task [for a similar approach, see 51 , 52 ]. Participants’ performance was around 1 at the beginning of the task and changed as the task progressed.…”
Section: Methodsmentioning
confidence: 99%
“…Although H + -producing and consuming steps are seen, no autocatalysis pathway has been identified so far. [45][46][47][48] Towards higher complexity in inorganic networks, multifeedback pH-oscillation systems, oscillation amplification, oscillation elimination, 49 beat phenomenon, 50 and synchronization 51 were achieved successfully in recent years. Subsequently, moving towards organic CRNs, Taylor and co-workers introduced the first experimental example of an organic-based pH-oscillator utilizing the base-catalysed dehydration of methylene glycol as a source of positive feedback (OH À autocatalysis) This journal is © The Royal Society of Chemistry 2023 coupled with the base-catalysed hydrolysis of gluconic acid d-lactone (d-GL) for negative feedback (H + production).…”
Section: History Of Oscillatory Reaction Network and Ph-feedback Reac...mentioning
confidence: 99%